2013
DOI: 10.3758/s13415-012-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts as aversive signals: Conflict priming increases negative judgments for neutral stimuli

Abstract: Botvinick, Cognitive, Affective, & Behavioral Neuroscience 7:356-366 (2007) recently suggested that competing theories of the monitoring function of the anterior cingulate cortex (ACC) for cognitive control might converge on the detection of aversive signals in general, implying that response conflicts, a known trigger of ACC activation, are aversive, too. Recent evidence showing conflict priming (i.e., faster responses to negative targets after conflict primes) directly supports this notion but remains inconc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
139
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 63 publications
20
139
2
3
Order By: Relevance
“…The hypothesis that the ACC monitors aversive signals has been supported by neuroimaging (Eisenberger, Lieberman, & Williams, 2003;Rainville, 2002;Singer et al, 2004) and behavioral (Dreisbach & Fischer, 2012;Fritz & Dreisbach, 2013;Schouppe, De Houwer, Ridderinkhof, & Notebaert, 2012) studies.…”
mentioning
confidence: 87%
“…The hypothesis that the ACC monitors aversive signals has been supported by neuroimaging (Eisenberger, Lieberman, & Williams, 2003;Rainville, 2002;Singer et al, 2004) and behavioral (Dreisbach & Fischer, 2012;Fritz & Dreisbach, 2013;Schouppe, De Houwer, Ridderinkhof, & Notebaert, 2012) studies.…”
mentioning
confidence: 87%
“…Yet, existing empirical support for MCC involvement in conflict costs have largely relied upon explicit manipulations of cognitive effort, and not conflict per se [2][3][4][5] . While some studies have demonstrated aversion-inducing effects of response conflict, these studies did not examine the neural mechanisms by which this effect is instantiated 2,6,7 . Here we demonstrate that response conflict acts as a cost during reinforcement learning by both diminishing reward value and boosting punishment aversion.…”
mentioning
confidence: 99%
“…Jika dikaitkan dengan teori feedback loops (Carver & Scheier, 1982), selama fase Testing dari siklus TOTE (Test-OperateTest-Exit), keberadaan afek negatif dibutuhkan dalam kadar tertentu agar selfcontrol dapat teraktivasi. Dalam sebuah studi, subjek cenderung mengidentifikasi target yang sebetulnya netral (kata-kata berbahasa Jerman dan Cina) sebagai stimulus negatif setelah diinduksi dengan tugas self-control sederhana berupa incongruent Stroop task (Fritz & Dreisbach, 2013). Afek negatif, rasa sakit, dan selfcontrol berada pada area anterior cingulate cortex yang membantu subjek menilai sejauh mana suatu stimulus berpotensi menghasilkan imbalan dan hukuman, serta merencanakan respons adaptif yang harus segera ia tampilkan (diskusi lebih lanjut, lihat Medford & Critchley, 2010).…”
Section: Diskusiunclassified